A negative nontreponemal and/or specific antitreponemal IgM test does not exclude active infectious syphilis: evidence from a rabbit infectivity test. Issue 31 (August 2016) - Lin, Li-Rong; Tong, Man-Li; Gao, Kun; Zhu, Xiao-Zhen; Fan, Jin-Yi; Zheng, Wei-Hong; Li, Shu-Lian; Lin, Hui-Ling; Liu, Li-Li; Yang, Tian-Ci
Abstract: Background: The diagnostic criteria for active infectious syphilis in the clinic are important matter of controversy and debate. So far, clinicians habitually do use the negative results of the nontreponemal and/or the specific antitreponemal IgM as the evidences of disease-free or active infection-free status. Method: We present a case study involving a patient who was admitted to Zhongshan Hospital because of cerebral infarct. Clinical examination indicated he had a history of latent syphilis with negative nontreponemal and specific antitreponemal IgM tests. The cerebrospinal fluid sample from the patient was inoculated into seronegative New Zealand rabbit. Results: Motile Treponema pallidum was detected by a rabbit infectivity test in the patient's cerebrospinal fluid. This syphilis strain was confirmed by DNA subtyping form of "centers for disease control subtype/tp0548 sequence type", and the strain type was 14d/f. Treatment with benzathine penicillin provided no apparent benefit, but treatment with aqueous crystalline penicillin G, especially recommended for neurosyphilis, led to disease regression. No evidence of cerebral infarct was observed during a 2-year follow-up period. Conclusion: The definitive differential diagnosis of active infectious syphilis should be reconsidered. Moreover, selecting the appropriate penicillin preparation is important because T pallidum can reside in sequestered sites. It is necessary to treat a patient with known invasion of the central nervous system with aqueous crystalline penicillin G, if previous treatment for syphilis failed and patients had some clinical neurological presentation that is otherwise unexplained, but that could represent neurosyphilis. Additional studies are needed to confirm the results in other syphilis patients.